The good, the bad and the ugly of Islamic credit cards / Zaimy Johana Johana and Mohd Zainee Hussain - Hussain, Mohd Zainee; Johana, Zaimy Johana (Universiti Teknologi MARA, 2021)
The Malaysian Islamic financial services have developed and thrived in the competitive domestic and global financial market, especially in the last three decades. The government has provided the industry conducive enabling environment to catalyse the industry growth and development. Islamic finance has gained prominence and been identified as the growth area in the nation's financial sector. With a range of innovative shariah compliant products and services, the halal financial services have gained market acceptance from both Muslims and non-Muslims alike, albeit with different acceptance levels according to the products. Specifically, to a certain degree, it appears that the market has been more receptive of other Islamic financial services such as loans for various purposes including purchases of securities, properties, vehicles; working capital and even personal loans than the credit cards. Additionally, slower growth, lower market share and performance of Islamic credit cards visa-vis conventional credit cards, and other Islamic financial products merit further scrutiny. A better analysis to understand the issues pertinent to Islamic credit cards' growth.